2009
DOI: 10.1590/s1517-83822009000200009
|View full text |Cite
|
Sign up to set email alerts
|

Detection of methicillin resistance and slime factor production of Staphylococcus aureus in bovine mastitis

Abstract: This study aimed to detect methicillin resistant and slime producing Staphylococcus aureus in cases of bovine mastitis. A triplex PCR was optimized targetting 16S rRNA, nuc and mecA genes for detection of Staphylococcus species, S. aureus and methicillin resistance, respectively. Furthermore, for detection of slime producing strains, a PCR assay targetting icaA and icaD genes was performed. In this study, 59 strains were detected as S. aureus by both conventional tests and PCR, and 13 of them were found to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
74
3
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(95 citation statements)
references
References 38 publications
12
74
3
6
Order By: Relevance
“…Genotypic characterization of S. aureus was performed by amplification of coagulase (coa) (Hookey et al, 1998) and species specific (nuc) (Ciftci et al, 2009) genes. The analysis of virulence factors comprised the detection of the following genes: icaA and icaD (Vasudevan et al, 2003) implicated in the production of slime; fnbA and fnbB that codifies fibronectin binding proteins; cap5 and cap8 related to the expression of capsule (El-Sayed et al, 2006) and the hemolysin genes hlA and hlB (Nilsson et al, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…Genotypic characterization of S. aureus was performed by amplification of coagulase (coa) (Hookey et al, 1998) and species specific (nuc) (Ciftci et al, 2009) genes. The analysis of virulence factors comprised the detection of the following genes: icaA and icaD (Vasudevan et al, 2003) implicated in the production of slime; fnbA and fnbB that codifies fibronectin binding proteins; cap5 and cap8 related to the expression of capsule (El-Sayed et al, 2006) and the hemolysin genes hlA and hlB (Nilsson et al, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…No teste com o Agar Vermelho Congo, apenas 2,77% dos isolados foram considerados positivos, resultado inferior ao encontrado por Freeman, Falkiner e Keane (1989), que detectaram a produção de biofilme em 77,78% dos isolados de SCN estudados. Ciftci et al (2009), ao estudarem a produção de biofilme em Staphylococcus aureus de mastite bovina, encontraram 37,2% de isolados positivos para o teste do Agar Vermelho Congo, enquanto que para a PCR foi observado que 25,42% dos S. aureus possuíam os genes icaA e icaD. Freeman, Falkiner e Keane (1989), propuseram o Agar Vermelho Congo como método alternativo para detectar a produção de biofilme.…”
Section: Resultsunclassified
“…Several studies have reported a higher frequency of distribution of the ica genes and slime production in Staphylococcus isolates from milk (Melo et al, 2013;Rumi et al, 2013;Ciftci et al, 2009), meat, and contact surfaces in processing plants (Schlegelová et al, 2008), indicating the virulence potential of the strains evaluated.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have reported higher frequency of distribution of the ica genes in Staphylococcus isolates from foods (Melo et al, 2013;Rumi et al, 2013;Ciftci et al, 2009;Rode et al, 2007;Møretrø et al, 2003).…”
Section: Introductionmentioning
confidence: 99%